2020
DOI: 10.3390/cancers12113272
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference between Rheumatoid Arthritis and Breast Cancer in East Asian and European Population: A Two-Sample Mendelian Randomization

Abstract: Previous studies have been reported that the association between rheumatoid arthritis (RA) and breast cancer remains inconclusive. A two-sample Mendelian randomization (MR) analysis can reveal the potential causal association between exposure and outcome. A two-sample MR analysis using the penalized robust inverse variance weighted (PRIVW) method was performed to analyze the association between RA and breast cancer risk based on the summary statistics of six genome-wide association studies (GWAS) targeting RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Regarding breast cancer, previous observational studies have consistently found a lower risk of breast cancer in RA patients than in women without this disease [29][30][31]. An MR study based on data from the BCAC, Biobank Japan, and Consortium of Investigators of Modifiers of BRCA1/2 also found that genetically proxied RA liability based on 25 SNPs was inversely associated with breast cancer in the East Asian population [13]. Nevertheless, this inverse association was not observed in the European population in our analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding breast cancer, previous observational studies have consistently found a lower risk of breast cancer in RA patients than in women without this disease [29][30][31]. An MR study based on data from the BCAC, Biobank Japan, and Consortium of Investigators of Modifiers of BRCA1/2 also found that genetically proxied RA liability based on 25 SNPs was inversely associated with breast cancer in the East Asian population [13]. Nevertheless, this inverse association was not observed in the European population in our analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, this method can minimize reverse causality since germline genotypes are unaffected by the onset and progression of the disease. A recent MR study found a protective association of genetic liability to RA and breast cancer risk in an East Asian population [13]. However, the MR associations of RA with risk of sitespecific cancers have not been explored in a systematic way.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting pathway enrichment analysis evidenced that the HGsT10 genes are majorly involved in bladder cancer, IL-17 signaling pathway, and ECM-receptor interaction in rheumatoid arthritis (RA). Ahn et al analyzed the association between breast cancer and RA using mendelian randomization (MR) analysis and reported that the underlying mechanism between these two diseases is still unclear [82].…”
Section: Discussionmentioning
confidence: 99%
“…The direct association between RA and infections/dysbiosis is more controversial and may result from the inclusion or not of the HLA locus in the analysis [ 18 , 99 ]. At the opposite, the MR approach has failed to establish a causal link with osteoporosis, vitamin D levels, atrial fibrillation, ischemic stroke, dyslipidemia, lung and breast cancer [ 14 , 18 , 34 , 35 , 40 , 42 ]. These co-founding effects can be related to the medications used and/or tobacco smoking.…”
Section: Il6/crp/sil6r/il1ra Pathway To Drive Chronic Inflammationmentioning
confidence: 99%